A life story forged by successive migrations: the case of Lucia - Machado, Ida Lucia (Revista da ABRALIN, 2021)
The aims of this article are divided in two: (i) show that life stories of migrants are currently necessary because they contemplate a discursive look that is at once social, historical and psychological; (ii) to investigate the identity “mysteries” of the protagonist and narrator of the novel Lucia, written by Olga Canllo Salomon, which tells the life of a poor Argentinian girl who, through displacements/migrations, found her place in the world after being forced to flee the military regimen that ruled her country in the 1970s. This female character fits into what I call “transclass subjects” because she went through life’s hardships hoping to find something better. The article relies on the theoretical convergence of life stories according to Machado (2018; 2019) and the Semiolinguistics proposed by Charaudeau (1983; 2006), to which I also add the ideas of Cyrulnik (2015) to explain/apply the notion of resilience, a feature of the novel’s female protagonist. I hope this article serves as testimonial of the research I have been conducting for some years and to which I now add the figure of migrants. Finally, excerpts of Lucia are cited to illustrate the imaginaries of beliefs of her homeland as well as her emotions, fears, and audacity